Implementation competences as an attribute of executive employees of the flexible organisation - an attempt of their assessment among manufacturers of the agricultural machinery sector = Kompetencje implementacyjne jako atrybut pracowników wykonawczych elastycznej organizacji - próba ich oceny wśród wytwórców sektora maszyn rolniczych - Nogalski, Bogdan; Niewiadomski, Przemysław (Zielona Góra: Faculty of Economics and Management Press)
Based on theoretical knowledge, own professional experience and conducted research, according to the authors, the paper's objective is to develop and empirically verify the theoretical model of implementation competences of the executive employees of manufacturing companies of the agricultural machinery sector.
Keywords: kompetencje implementacyjne; elastyczność; luka kompetencyjna; doskonalenie; implementation competences; flexibility; competence gap; improvement